2020
DOI: 10.23822/eurannaci.1764-1489.121
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of allergic bronchopulmonary aspergillosis in cystic fibrosis patients using two different diagnostic criteria

Abstract: Objective: There are different diagnostic criteria for the diagnosis of Allergic bronchopulmonary aspergillosis (ABPA) in CF patients. In this present study we evaluated the prevalence of ABPA in Iranian CF patients by two more usual diagnostic criteria as ISHAM working criteria (A) and CF Foundation Consensus Conference criteria (B). Methods: Eighty six CF patients were included in the study. All CF patients underwent for Aspergillus skin prick test (AST), Aspergillus-specific IgE (sIgEAf) and Aspergillus-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
(16 reference statements)
0
13
0
1
Order By: Relevance
“…The latest globally implemented diagnostic criteria were proposed by the International Society for Human and Animal Mycology (ISHAM) Working Group in 2013. Their criteria include (1) history of asthma or CF; (2) positive Aspergillus skin testing with a wheal diameter greater than 3 mm or elevated IgE against A. fumigatus above 0.1 kUA/L, and elevated total serum IgE above 1000 IU/mL; (3) at least two of the following: (a) precipitating serum antibodies against A. fumigatus or elevated serum Aspergillus IgG, (b) mucous plugging or central bronchiectasis seen on chest imaging, or (c) total eosinophil count greater than 500 cells/mL in steroid-naïve patients [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest globally implemented diagnostic criteria were proposed by the International Society for Human and Animal Mycology (ISHAM) Working Group in 2013. Their criteria include (1) history of asthma or CF; (2) positive Aspergillus skin testing with a wheal diameter greater than 3 mm or elevated IgE against A. fumigatus above 0.1 kUA/L, and elevated total serum IgE above 1000 IU/mL; (3) at least two of the following: (a) precipitating serum antibodies against A. fumigatus or elevated serum Aspergillus IgG, (b) mucous plugging or central bronchiectasis seen on chest imaging, or (c) total eosinophil count greater than 500 cells/mL in steroid-naïve patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple diagnostic criteria, which include a combination of radiological findings as well as serologic and immunologic studies, in order to establish the diagnosis of ABPA. The vast majority of them either include the presence of asthma or CF as an integral part of the diagnostic algorithm, or the criteria is specifically made for patients with CF [2,3]. However, an increasing number of reported ABPA cases do not strictly satisfy all diagnostic criteria or are presented atypically, which causes delays in diagnosis and subsequent initiation of appropriate medical treatment [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many diagnostic criteria for ABPA, Maleki et al showed that there was no significant differences on the reported rate of ABPA prevelance between the Cystic Fibrosis Foundation and International Society for Human and Animal Mycology (ISHAM) diagnostic criteria (32).…”
Section: Diagnosismentioning
confidence: 99%
“…Maleki et al found no significant effect on the reported prevalence of ABPA in CF patients depending on the applied criteria [ 45 ].…”
Section: Diagnosis Of Abpa In Patients With Cfmentioning
confidence: 99%